INVESTIQATION OF THE STABILITY OF SOLUTIONS OF DIFFERENTIAL EQUATIONS WITH IMPULSE ACTION BU THE SECOND LIAPUNOV’S METHOD - Гургула, Степан Іванович; Собкович, Роман Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Criteries of stability, asymptotic stability and non-stability of simple solution in an analogy to those according to secondary Liapunov’s method for systems of ordinary differential equations, were issued for a system of differential equations with impulsive action on the given hyperplanes of extended phase spase.